Viver e morrer: uma análise sobre a cofiguração sócio-familiar na freguesia de Limoeiro-CE, (1870 a 1880) - Chaves, Elisgardênia de Oliveira (2009)
Living and dying: an analysis of the socio-family configuration in parish of the Limoeiro – CE (1870 to 1880) is a study to understand the characteristics of building population and the types and forms of family organization more present in this society. In the decade of 1870, the configuration of socio-family in the parish of Limoeiro do Norte was characterized by higher rate of the free people in relation to the slaves, by higher rate of the brown people in relation to white people and higher rate of white people in relation to black people. The division by gender was characterized by a small majority for men. This social diversity was felt also in the family organization, which forms over the concept and ideal of marriage ranged from nuclear families, matrifocal and extensive. The religious and economics precepts influenced in the selection or rejection of same months to perform the marriage, the conceptions, the births and the baptisms. The die of the people by multiple factors occurred primarily on children up to seven years old and it was remarkably increased during the drought of 1877-1879. Altogether the Christian sacraments permeated highlights around the life and the death of the limoeirense society.